Accreditation: One way to standardize education - Vargas Porras, Alicia E. (2011)
The accreditation comes at low interest Latin American countries clearly marked by thesocioeconomic and political situation begins toshape in the eighties, where globalizationactivities requires global responses to various human actions. Higher education, in thatcontext begins to face a series of lawsuitsto redefine his work and one of them is the need for self-evaluation and self-regulation processes leading to accreditation.In this paper we analyze the origins, intentions and interests that drive processes leading to accreditation in education systemstop Latin American countries. As educational policy process, assessment is marked byintentions and interests that indicate a certainway for educational and, in that sense,Some also point hegemonic traits tend to homogenize the higher educationLatin American countries. Also discussed boththe discourses of quality manufacturing genealogy criteria that derive from there and founddirecting some evaluative processes. We concludewith a reflection on a concept of qualityto build, considering it our duty totowards strengthening the development ofour societies.